Altering misconceptions: how e-rebuttal texts on Newton’s laws reconstructs students’ mental models - Suhandi, Andi; Samsudin, Achmad; Fratiwi, Nuzulira Janeusse; Nurdini, Nurdini; Feranie, Selly; Purwanto, Muhammad Guntur; Linuwih, Suharto; Coştu, Bayram (Frontiers in Education, 2025)
This study aims to explore how e-rebuttal texts on Newton’s laws can reconstruct students’ mental models by altering existing misconceptions. A mixed methods approach (quantitative and qualitative) was used in the research. Participants were 31 students (15 boys and 16 girls, aged 15–16 years) in the 10th grade of one public high school in Sukabumi, West Java, Indonesia. The instrument used Multi-representation on Tier Instrument of Newton’s laws (MOTION), consists of 36 subject matter questions about Newton’s First Law, Newton’s Second Law, Newton’s Third Law, and the type of forces. The data were analyzed using the categories of conception, mental model, and correction of a mental model. The result shows positive changes in each mental model from the pre-test to the post-test. The rate of correction in students’ mental models from pre-test to post-test occurred primarily in the Acceptable Correction (ACo) category. It was concluded that e-rebuttal texts can be used to reconstruct students’ mental models in conceptual change to become Scientific (SC) models. Other researchers may use learning models and strategies to involve students in groups to facilitate the discussion process.